Anti-Listeria activity of Lactococcus lactis subsp. lactis LAB3 cells entrapped in alginate beads: effects of inoculum size, alginate bead formulation, and atmosphere composition - Yan He; Pascal Degraeve; Nadia Oulahal (Frontiers in Microbiology)
Bioprotective Lactococcus lactis LAB3 cells that produce bacteriocin-like substances were entrapped in 4% (w/w) sodium alginate matrices, either with or without 10% (w/w) sodium caseinate. The effects of bead formulation—alginate alone or combined with caseinate, with or without the addition of 20% (w/w) MRS broth or M17 broth—on the culturability of Lc. Lactis LAB3 cells within the beads and their anti-Listeria activity were assessed over 12 days of storage at 30 °C in closed bottles. Calcium–alginate–caseinate beads supplemented with MRS broth proved most effective in preserving both culturability and anti-Listeria activity. Inoculum size (~106 or ~108 CFU mL−1 initially) also played a role: only the higher initial inoculum yielded significant anti-Listeria activity after 12 days at 30 °C, despite a gradual decline over time, likely due to rapid nutrient depletion. In order to evaluate the feasibility of combining modified-atmosphere packaging with the addition of the Lc. lactis LAB3 bioprotective strain for preserving perishable foods, a prerequisite was to evaluate whether anti-Listeria activity persisted after 4 days of storage at 30 °C in calcium–alginate–caseinate beads containing either MRS or M17 broth under three different atmospheres. Beads entrapping Lc. lactis LAB3 cells stored in 20% (v/v) O2–80% (v/v) N2 or in 60% (v/v) O2–40% (v/v) N2 retained their anti-Listeria activity, whereas storage in 20% (v/v) CO2–80% (v/v) N2 impaired this activity.